Comparison of analytical performances between clot waveform analysis and FibWave in edoxaban‐treated patients and healthy controls. Issue 7 (4th November 2022) - Evrard, Jonathan; Siriez, Romain; Bouvy, Céline; Favresse, Julien; Yildiz, Halil; Hainaut, Philippe; Mullier, François; Dogné, Jean‐Michel; Douxfils, Jonathan
Abstract: Introduction: The activated partial thromboplastin time (aPTT) and the prothrombin time (PT) are widely available coagulation parameters which are however poor predictors of the anticoagulant effect of direct oral anticoagulants (DOACs). Some coagulometers use the clot waveform analysis (CWA) to assess the clotting time but mainly based on a unique parameter. The improvement of these methodologies and the evaluation of the other waveform parameters may increase the sensitivity to DOACs. Objectives: To assess the performance of an improved clot waveform an method (i.e. FibWave) to detect the impact of edoxaban on the coagulation and the fibrinolytic systems. Methods: Seventy‐one samples from patients treated with edoxaban collected at minimum concentration (CTROUGH ) and/or maximum concentration (CMAX ), and 45 control samples were included. The aPTT‐ and PT‐based CWA as well as the FibIn, FibEx, and FibLysis methodologies of the FibWave were implemented and performed on an ACL‐TOP 700. Results: PT and FibEx clotting time were strongly correlated to edoxaban concentration (Pearson r = 0.80 and 0.89, respectively). The FibEx clotting time allowed a better discrimination for samples with 30 and 50 ng/ml of edoxaban compared to PT (cutoffs of 96.5 and 114.2 s for the FibEx versus a unique cutoff of 13.1 s for the PT). The fibrinolytic process was impaired in the presence of edoxaban in a dose‐dependent manner. Conclusion: FibEx is more sensitive than aPTT‐ and PT‐based CWA for the detection of the clinically relevant anticoagulant level of edoxaban.